2020
DOI: 10.3390/mi11100946
|View full text |Cite
|
Sign up to set email alerts
|

Application of Stereolithography Based 3D Printing Technology in Investment Casting

Abstract: Advanced methods for manufacturing high quality parts should be used to ensure the production of competitive products for the world market. Investment casting (IC) is a process where a wax pattern is used as a sacrificial pattern to manufacture high precision casting of solid metal parts. Rapid casting is in turn, a technique that eases the IC process by combining additive manufacturing (AM) technologies with IC. The use of AM technologies to create patterns for new industrial products is a unique opportunity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 102 publications
1
62
0
1
Order By: Relevance
“…Ishida et al [21] tested the ability of different manufacturing methods to create dimensionally accurate full dental crowns, and they showed that all the methods had their respective drawbacks. The RIC processes, mainly using Stereolithography (SLA) can be found in a review [22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ishida et al [21] tested the ability of different manufacturing methods to create dimensionally accurate full dental crowns, and they showed that all the methods had their respective drawbacks. The RIC processes, mainly using Stereolithography (SLA) can be found in a review [22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The alternative to 3D printing would be to make the wax models manually, in which case the printing process allowed us to obtain greater reproducibility and better dimensional tolerances. Additionally, it should be remembered that SLA technology is also used to produce models intended for the traditional lost-wax casting process [16], allowing us in this case to obtain finished components with surface roughness identical to that obtained with wax models. However, the SLA technique is limited to small components due to the large deformations that would occur during the resin printing process and is usually used in the goldsmith and medical sectors [17], and the cost of the resin is also usually higher than that of FDM printing filaments.…”
Section: D Printing For Supporting the Component Manufacturing Processmentioning
confidence: 99%
“…Although stereolithography provides a practical technical way for the efficient and high-quality manufacturing of silica ceramic parts [22,23], there exist some research difficulties. Firstly, the forming mode of layer-by-layer curing can easily cause larger linear shrinkage [24], which will not only affect the mechanical properties of ceramic parts, but also limit the wide application of ceramic products [25,26].…”
Section: Introduction mentioning
confidence: 99%